Machines group and load balancing: an industrial case. Issue 13 (2019) - Berthier, A.; Yalaoui, A.; Chehade, H.; Yalaoui, F.; Amodeo, L.; Coquelet, G.
Abstract: This paper presents a problem from the textile industry wich consists of designing the layout of a knitting workshop. Machine groups are created to balance the operators' workload and the layout is designed to create group cells. New models are proposed in this paper with two approaches. The first is an aggregated model and the second one proposes a two-step sequential method. The two models were implemented using CPLEX-ILOG software and compared to provide preliminary results. Future directions for research are outlined to further address this issue.